2008
DOI: 10.1007/s10660-008-9017-x
|View full text |Cite
|
Sign up to set email alerts
|

Designing a secure e-tender submission protocol

Abstract: This paper investigates the fundamental difference between a simple e-tender box and a traditional physical tender box, and highlights a series of security traps created by the functional differences. Based on our findings, we have defined the security requirements for an e-tender submission protocol. We also discuss functional limitations of cryptographic technologies. As a result, two secure e-tender submission protocols are proposed which enable a secure e-tender submission. Protocols are assumed to run und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Patil et al (2016) highlighted the process/activities involved prior to the e-tender in a construction project and suggested the importance of e-tender process over the traditional tendering process. Some authors have demonstrated the importance of designing a secure submission protocol to minimize the fraud during the e-tendering process (Du et al , 2008; Horne et al , 2018; Lou and Alshawi, 2009). Lou and Alshawi (2009) advocate the benefits of e-tendering in the reduction of costs from tender documentation production, a shortened tender period and a more systematic and progressive method of working.…”
Section: Introductionmentioning
confidence: 99%
“…Patil et al (2016) highlighted the process/activities involved prior to the e-tender in a construction project and suggested the importance of e-tender process over the traditional tendering process. Some authors have demonstrated the importance of designing a secure submission protocol to minimize the fraud during the e-tendering process (Du et al , 2008; Horne et al , 2018; Lou and Alshawi, 2009). Lou and Alshawi (2009) advocate the benefits of e-tendering in the reduction of costs from tender documentation production, a shortened tender period and a more systematic and progressive method of working.…”
Section: Introductionmentioning
confidence: 99%